CLINICAL UTILITY OF CAVeA2T2 SCORE FOR ASSESSING THE SURVIVAL OF BRACHIOCEPHALIC ARTERIOVENOUS FISTULA - Usman, Rashid; Malik, Hammad; Mehmood, Mudassar; Anwar, Muhammad Waseem; Shahab, Amna (Journal of Ayub Medical College Abbottabad, 2020)
Background: There are not many error proof clinical scores to assess the native dialysis access. CAVeA2T2 score is a recent tool in use. Objective of the study is to assess the clinical utility of CAVeA2T2 scoring system in predicting the survival rate of brachiocephalic arteriovenous fistula (BC-AVF). Methods: All consecutive patients fulfilling the inclusion criteria for BC-AVF from January 2016 to January 2018 were included. According to their CAVeA2T2 score they were divided into two groups (Group A: < 2 and Group B: ‰¥2). Cumulative primary and secondary patency survival of BC-AVF for both groups were measured. Results: A total of 112 BC-AVFs were analysed. Mean age was 42±SD 14 years (M: F =5:1). Mean CAVeA2T2 score was 1.45±1.8. In terms of primary patency, there was no statistically significant difference between two groups (p=0.074, p = 0.229 and p=0.357 at 6 weeks, 6 months and 12 months respectively). However, the difference was significant in terms of secondary patency (p=0.002, p=0.036 and p=0.032 at 6 weeks, 6 months and 12 months respectively). On comparing the cumulative survival between two groups; a significantly low primary patency rate survival (Log Rank x2 = 12.9, p-value = 0.001) and secondary patency rate survival (Log Rank x2 = 7.6, p-value = 0.001) of BC-AVF was found in Group B. Conclusion: We found CAVeA2T2 score an easily applicable and useful tool to assess the patency and survival of BC-AVF. Patients have a poor patency and significantly low survival rate when their CAVeA2T2 score was ‰¥2. Keywords: Fistula survival; Patency rate; Score; Arteriovenous fistula